Responsive love - Waldenfels, Bernhard (Primerjalna književnost, 2016)
Love is described from the perspective of responsive phenomenology. It appears as a sort of pathos, as a doubling of one's own desire, as an experience marked by the alienness of oneself and that of the Other. Like any creative response love has to be invented. It means giving what one does not have.
Keywords: fenomenologija; ethics; etika; ljubezen; love; patos; Drugi; odziv; želja; tujost